Pengembangan Jiwa Kewirausahaan Siswa Sekolah Dasar melalui Literasi Keuangan dan Eksplorasi Profesi Kreatif di SDN 3 Tangkiling - Yuliantina, Devi; Putri Irianti Sintaman; Muhammad Achiril Haq; Rihwanun Nufuts; Purwitasari Purwitasari (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity was implemented at SDN 3 Tangkiling to cultivate an entrepreneurial mindset among elementary school students by integrating financial literacy and exploring creative professions. The program emphasized enhancing students' comprehension of fundamental financial principles through socialization activities and rudimentary buying and selling simulations using play money. The “Mini Shop” activity was implemented to facilitate students' learning about the value of money, the distinction between needs and wants, and the importance of saving. This activity was designed using an active and contextual learning approach, which aligns with the characteristics of elementary school students and the principles of the Merdeka Curriculum, emphasizing character building, independence, and creativity. Additionally, the exploration of creative professions was undertaken through the implementation of role-playing and interactive discussions, thereby introducing a variety of occupations and cultivating an interest in entrepreneurship from an early age. The outcomes of the activity indicated that students exhibited increased enthusiasm and comprehension of fundamental financial concepts and demonstrated an interest in elementary entrepreneurial activities. It is anticipated that this program will evolve into an inspirational learning model for instilling financial literacy and entrepreneurial spirit at the elementary school level.